Influence of larval density on biological fitness of Ephestia kuehniela Zeler (Lepidoptera Pyralidae ) - Xu, J.; Wang, Q.; He, X.Z. (New Zealand Plant Protection, 2007)
Mediterranean flour moth Ephestia kuehniella is a cosmopolitan pest of stored products and its eggs are widely used to rear parasitoids and predators for biological control programmes This experiment investigated how larval population density affected the survival rate and reproductive output of this species under four rearing densities (1 larva per 2 g food per vial; or 100 500 or 1000 larvae per 50 g food per jar) The survival rate and reproductive output significantly decreased (P